Filipino living-room furniture preferences : a sampling the San Francisco Del Monte community - Yamut, Robert Vincent Tablante; Florendo, Raquel Baltazar (1991.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis(BID)--University of the Philippines Diliman
Keywords: Living room furniture